The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1002/1097-0142(20010901)92:5<1251::aid-cncr1445>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Detection of tumor cells in the portal and peripheral blood of patients with colorectal carcinoma using competitive reverse transcriptase-polymerase chain reaction

Abstract: BACKGROUND In spite of many reports, it remains unclear whether the presence of tumor cells in circulating blood flow predicts a poor prognosis. METHODS Competitive seminested reverse transcriptase‐polymerase chain reaction (RT‐PCR), a technique for the quantitative detection of tumor cells, was applied to detect the presence of tumor cells in portal and peripheral blood samples from 121 patients with colorectal carcinoma and to clarify their clinical significance. This technique can detect one carcinoembryoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 34 publications
1
13
1
Order By: Relevance
“…The 7700 Sequence Detector System (Applied Biosystems) was used for Real-time quantitative RT-PCR (32,33). Briefly, each RT-PCR reaction mixture (50 μl) included 250 ng of total RNA, 25 μl of Taqman Universal PCR Master Mix (Applied Biosystems), 0.5 μl of forward and reverse primer (10 μM), and 1.0 μl of corresponding Taqman probe (5000 nM).…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“…The 7700 Sequence Detector System (Applied Biosystems) was used for Real-time quantitative RT-PCR (32,33). Briefly, each RT-PCR reaction mixture (50 μl) included 250 ng of total RNA, 25 μl of Taqman Universal PCR Master Mix (Applied Biosystems), 0.5 μl of forward and reverse primer (10 μM), and 1.0 μl of corresponding Taqman probe (5000 nM).…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“…This observation may partially explain the negative conclusions reached by other authors, who suggested that the presence of circulating tumor cells might be of little value as a prognostic factor, because they appeared not to be associated with conventional prognostic factors, namely the presence of metastatic disease. 20 The findings here of a significant association between increased sE-selectin and positive CEA mRNA-expressing cells in the peripheral blood of patients with low-grade inflammatory status (as evidenced by increased levels of TNF-a) fuel the hypothesis that circulating tumor cells may, indeed, represent a prognostic factor, but only in those patients in whom they are capable of triggering the molecular changes demonstrated in the studies cited above, 6,7 and suggest that circulating tumor cells might be responsible for macrophage activation in vivo, release of proinflammatory cytokines, and up-regulation of vascular E-selectin, which can be detected in its soluble form on shedding from the endothelial cell surface. This hypothesis is also consistent with the finding that the highest sEselectin levels were detected in patients highly expressing CEA mRNA and with positive TNF-a levels compared with patients with negative levels of both variables.…”
Section: Discussionmentioning
confidence: 58%
“…The association of tumorspecific mRNA detection in the peripheral blood with the various clinicopathological parameters has been a matter of significant debate. There is reported evidence to a significant association of disseminated cancer cell detection to advance stage and lymph node metastasis [21,45]. On the other hand, there are studies that no correlation can be detected between the CEA mRNA detection and the clinicopathological characteristics of the disease [7].…”
Section: Discussionmentioning
confidence: 99%